S146 Characterisation of anti-synthetase syndrome (ASS), initially presenting to respiratory services as interstitial lung disease (ILD) of unknown cause. (December 2018) - Barratt, SL; Iftikar, H; McMillan, M; Edey, A; Adamali, H; Gunawardena, H
Abstract : Introduction: The therapeutic management of CTD-ILD and idiopathic forms differs widely, thus accurate diagnosis is essential. Several myositis-specific and myositis-associated antibodies (MSA/MAA) are now detectable that may associate with ILD. We wished to: 1) evaluate the use of comprehensive autoantibody testing to help differentiate idiopathic ILD from anti-synthetase syndrome (ASS) associated-ILD and 2) determine if there were differences in clinical characteristics of ASS-ILD patients presenting to respiratory versus rheumatology services. Method: We retrospectively analysed the clinical characteristics and antibody profiles of ILD patients referred between Jan 2015 and July 2017. The clinical characteristics of all ASS-ILD patients were collated. Results: Twenty-five patients (11 M: 14 F), referred initially to respiratory services as ILD of unknown cause, were diagnosed with ASS, representing 3.1% of new ILD referrals received (based on 27 new referrals/month). Patients were significantly younger than randomly selected comparator cohorts of IPF and unclassifiable (u) ILD patients (ASS patients median age 59 years (IQR 50–69.5) vs IPF 78 years (IQR 73.5–82) (p<0.0001) and uILD 70 years (IQR 57.5–82) (p<0.05) (n=25 each). Although 76% of the ASS cohort were ANA negative (19/25), co-existent cytoplasmic staining was detected using cell immunofluorescence in 84% (21/25). For comparison, homogenous ANA positivity was detected in 13/25 IPF and in 7/25 uILD cohorts, in the absence of cytoplasmic staining. Anti Jo-1 antibodies were identified in 40% (10/25) of ASS patients (ENA positive). Specific MSAs were detected in a further 11 patients (2 EJ, 4 PL7, 1 KS, 3 PL12, 1 OJ – ENA negative) using immunoblot techniques. ASS patients with ILD who initially presented to respiratory services were more likely to express non-Jo-1 MSAs (p<0.05) and less likely to present with clinically apparent myositis (p<0.01) compared to those who initially presented to rheumatology services (n=13) (See table 1). The extent of ILD at presentation was comparable between groups (p>0.06). Conclusions: A negative ANA screen does not necessarily indicate autoantibody negativity. Despite the presence of MSAs, ASS-ILD patients presenting to respiratory services were more likely to have an amyopathic phenotype. Comprehensive serological testing, including cell immunofluorescence, should be routinely considered in initial assessments of ILD patients.